2014
DOI: 10.1039/c4cc01984a
|View full text |Cite
|
Sign up to set email alerts
|

Vertically aligned ZnO@CuS@PEDOT core@shell nanorod arrays decorated with MnO2 nanoparticles for a high-performance and semi-transparent supercapacitor electrode

Abstract: Hybrid nano-architectures with high electrochemical performance for supercapacitors have been designed by growing hierarchical ZnO NRs@CuS@PEDOT@MnO2 core@shell heterostructured nanorod arrays on ITO/glass substrates. This hybrid nano-structured electrode exhibits excellent electrochemical performance, with a high specific areal capacitance of 19.85 mF cm(-2), good rate capability, cycling stability and diffused coloured transparency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 30 publications
1
39
0
Order By: Relevance
“…In the past few years, it has been well demonstrated that the development of binary or ternary nanocomposites of these different capacitive materials become the novel approaches to control and optimize the structures and physical and mechanical properties of electrode materials, in order to achieve the enhanced performance for supercapacitors . Various hybrid systems like MO x /CNTs , CPs/GO , CPs/CNTs , and MO x /CPs have been developed to improve the specific capacitance, stability, and energy density. However, the properties of composite electrodes depend not only upon the individual active components but also on the morphology and the interfacial characteristics.…”
Section: Materials For Flexible Supercapacitorsmentioning
confidence: 99%
“…In the past few years, it has been well demonstrated that the development of binary or ternary nanocomposites of these different capacitive materials become the novel approaches to control and optimize the structures and physical and mechanical properties of electrode materials, in order to achieve the enhanced performance for supercapacitors . Various hybrid systems like MO x /CNTs , CPs/GO , CPs/CNTs , and MO x /CPs have been developed to improve the specific capacitance, stability, and energy density. However, the properties of composite electrodes depend not only upon the individual active components but also on the morphology and the interfacial characteristics.…”
Section: Materials For Flexible Supercapacitorsmentioning
confidence: 99%
“…It has been widely applied as chemical sensors, Li-ion batteries, catalyst, solar cells and so on [15e21]. Several attempts have been made to explore CuS as an electrode material for supercapacitors due to its metallike electronic conductivity (10 À3 S cm À1 ) and high theoretical capacity (561 mAh g À1 ) [22,23]. However, it is not favorable for applications in supercapacitor because pure CuS is a semiconductor and has relatively low conductivity when compares to carbon nanomaterials and its volume change during cycling causes poor cycling stability.…”
Section: Introductionmentioning
confidence: 99%
“…However, to our best knowledge, there has only been limited study on CuS coated ZnO nanowire [26,27].…”
Section: Introductionmentioning
confidence: 95%